Note—A Prediction Model for Manufacturer Warranty Reserves - Thomas, Marlin U. (Management Science, 1989)
A model for predicting warranty reserves for manufactured units having exponential failures is extended for more general failure distributions. The model allows for discounting. Sample calculations are provided.